Uji In-Vitro Ekstrak Kulit Jengkol (Pithecellobium jiringa) sebagai Biofungisida terhadap Fusarium oxysporum, Colletotrichum capsici, dan Cercospora capsici pada Tanaman Cabai - Siswandi Siswandi; Retna Astuti; Maimunah Maimunah (Universitas Medan Area, 2020)
Research aims To determine the effectiveness of skin extract jengkol (Pithecellobium jiringa) effective as biofungisida against the disease-causing Fusarium wilt (Fusarium oxyospurum), Antraknosa (Colletotrichum capsici) and patches leaf (Cercospora capsici) on a red pepper plant (Capsicum annuum L.),This research was conducted at the Laboratory of Plant Protection, Faculty of Agriculture, University of Medan Area, Biopharmaceutical Laboratories Faculty of Pharmacy, University of North Sumatra, from March to May 2019. This research used non factorial completely randomized design with three replications. Factors treatment of skin extract concentration jengkol ie negative control (no treatment); positive control (synthetic fungicides 0.2%); and successive concentration is 10%; 20%; 30%; 40%; 50%; 60%; 70%; 80%; 90%; and 100%. The results showed that administrationjengkol skin extract effective for controlling fungal pathogens (Colletotrichum capsici, Fusarium oxysporum and Cercospora capsici) that cause disease in plants red chili.Jengkol bark extract at a concentration of 90% obtained the highest percentage inhibition Fusarum oxysporum as big as 78.43% Highly significant with bark extract treatment jengkol 10% and a negative control (no treatment), at a concentration of 20% jengkol skin extract obtained the highest percentage inhibition of Colletotrichum capsici 82.49% Highly significant with bark extract treatment jengkol 10%, negative control (no treatment) and at a concentration of 50% jengkol skin extract obtained the highest percentage inhibition Cercospora capsici as big as 83.43% Highly significant with bark extract treatment jengkol 10%, 20% jengkol bark extract, bark extract jengkol 30% and analytical results.